Peran Kemitraan Masyarakat dan Perusahaan Kelapa Sawit dalam Pengelolaan Limbah serta Implikasinya pada Kesehatan Lingkungan: Sebuah Telaah Pustaka - Saputra, Dhendi Novianto; Ritonga, Abdullah Ibrahim; Kastilon, Kastilon; Reflis, Reflis; Utama, Satria Putra (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
The development of the Indonesian palm oil industry has direct implications for the increasingly widespread cultivation of oil palm, both managed by small-scale companies and those managed by large-scale companies. This condition is directly proportional to the increase in the amount of solid waste and liquid waste produced from industrial activities. Solid waste and liquid waste can pollute the environment and endanger public health if not managed properly. This literature review aims to examine the role of partnerships between communities and the palm oil industry in managing palm oil waste and its implications for environmental health. Partnerships involve active community participation in planning, implementing, monitoring and evaluating waste management programs. The results of the literature review show that the partnership has had a positive impact, such as improving water and air quality and reducing the prevalence of environmentally related diseases. Apart from that, community empowerment programs in processing waste into economically valuable products also provide economic benefits. However, there are inhibiting factors such as low public awareness, limited human resources, and lack of other supporting facilities and infrastructure.